Avatars at Work and Play Collaboration and Interaction in Shared Virtual Environments - Schroeder, Ralph; Axelsson, Ann-Sofie.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Avatars at Work and Play brings together contributions from leading social scientists and computer scientists who have conducted research on virtual environments used for collaboration and online gaming. They present a well-rounded and state-of-the-art overview of current applications of multi-user virtual environments, ranging from highly immersive virtual reality systems to internet-based virtual environments on personal computers. The volume is a follow-up to a previous essay collection, 'The Social Life of Avatars', which explored general issues in this field. This collection goes further, examining uses of shared virtual environments in practical settings such as scientific collaboration, distributed meetings, building models together, and others. It also covers online gaming in virtual environments, which has attracted hundreds of thousands of users and presents an opportunity for studying a myriad of social issues. Covering both 'work' and 'play', the volume brings together issues common to the two areas, including: What kind of avatar appearance is suitable for different kinds of interaction? How best to foster collaboration and promote usable shared virtual spaces? What kinds of activities work well in different types of virtual environments and systems?
Transformed Social Interaction: Exploring the Digital Plasticity of Avatars -- Selective Fidelity: Investigating Priorities for the Creation of Expressive Avatars -- Analysis and Visualization of Social Diffusion Patterns in Three-Dimensional Virtual Worlds -- Collaborative Virtual Environments for Scientific Collaboration: Technical and Organizational Design Frameworks -- Analyzing Fragments of Collaboration in Distributed Immersive Virtual Environments -- The Impact of Display System and Embodiment on Closely Coupled Collaboration Between Remote Users -- The Good Inequality: Supporting Group-Work in Shared Virtual Environments -- Consequences of Playing Violent Video Games in Immersive Virtual Environments -- The Psychology of Massively Multi-User Online Role-Playing Games: Motivations, Emotional Investment, Relationships and Problematic Usage -- Questing for Knowledge-Virtual Worlds as Dynamic Processes of Social Interaction -- Play and Sociability in There: Some Lessons from Online Games for Collaborative Virtual Environments -- Digital Dystopia: Player Control and Strategic Innovation in the Sims Online.
Keywords: COMPUTER SCIENCE; SOFTWARE ENGINEERING; SOCIAL SCIENCES; COMPUTER SCIENCE; USER INTERFACES AND HUMAN COMPUTER INTERACTION; SPECIAL PURPOSE AND APPLICATION-BASED SYSTEMS; COMPUTERS AND SOCIETY; MEDIA DESIGN; SOCIAL SCIENCES, GENERAL